Blood Far Forward—a whole blood research and training program for austere environments. (10th January 2013) - Strandenes, Geir; Cap, Andrew P.; Cacic, Daniel; Lunde, Turid Helen Felli; Eliassen, Håkon Skogrand; Hervig, Tor; Spinella, Philip C.
Abstract : The Blood Far Forward (BFF) research program was established to conduct blood product efficacy and safety studies, donor performance studies, and research on optimal training methods to improve the safety of blood collection and transfusion performed by Norwegian Naval Special Operation Commando soldiers. The use of intravenous fluids for volume replacement during hemorrhagic shock is controversial, but it is currently the standard of care. In the far‐forward environment, large volume resuscitation for massive bleeding is a great challenge. Crystalloid and colloid solutions add weight and bulk to the medic's kit, require temperature sensitive storage, and should be warmed before infusion to prevent hypothermia. Excessive use of these solutions causes a dilutional coagulopathy, acidosis, and potentially increased inflammatory injury compared with blood products. Type‐specific whole blood from an uninjured combat companion on the other hand is almost always available. It is warm, replaces intravascular volume, and provides oxygen delivery and hemostatic capacity to prevent or treat shock and coagulopathy. Whole blood may be ideal for the resuscitation of combat casualties with hemorrhagic shock. BFF program pilot studies on use of platelet‐sparing leukoreduction filters, whole blood transport tolerance, donor performance, and autologous reinfusion of 24‐hour ambient temperature stored whole blood have been performed and suggest the feasibility of expanding whole blood use in resuscitation. If successful, the BFF program will change tactics, techniques, and procedures with a new lifesaving capability.